Existence of multiple solutions for a singular $ p(·) $-biharmonic problem with variable exponents - Ramzi Alsaedi (AIMS Mathematics)
In this work, we study a multiplicity result related to a $ p(τ) $-Biharmonic equation involving singular and Hardy nonlinearities. More precisely, we use the variational method to develop the analysis of the fibering map in the Nehari manifold sets to prove the existence of two nontrivial solutions for such a problem.